Islamic Religious Education Teachers' Strategies in Improving Learning Discipline - Tusyadiah, Nur Halimah; Utomo, Ainur Alam Budi; Fudholi, Agus (Jurnal Ilmiah Iqra', 2025)
TThis study aims to determine the level of learning discipline of grade X students majoring in mechanical engineering at SMK Jayabeka 01 Karawang. Using a qualitative approach with case studies, this study involves the Principal of the Curriculum, PAI Teachers, and Students as the main subjects. The data collected were in the form of interviews, direct observations at schools, and documentation. The results in this study are that the strategy of PAI teachers in improving the discipline of class X students at SMK Jayabeka 01 Karawang is by enforcing every discipline in the classroom or outside the school, giving strict punishment to every student who violates, giving praise to students who are active and diligent when in the school environment, which can improve learning discipline. Each teacher provides advice and offers good reminders to students. The obstacles for PAI teachers in improving student learning discipline are students who are unaware of their needs, students who frequently enter and exit the classroom, and students from low-income family backgrounds, which can result in them becoming unfocused and lacking discipline.